2021
DOI: 10.1108/jgoss-07-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain technology in financial services: a comprehensive review of the literature

Abstract: Purpose The purpose of this study is to thoroughly review studies that have used blockchain technology in financial services. This study will help provide a holistic framework that would highlight the current state and challenges of the blockchain in the financial services sector. Design/methodology/approach The objective of this study is to systematically examine and organize the current body of research literature that either quantitatively or qualitatively explored the use of blockchain technology in fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 80 publications
2
27
0
1
Order By: Relevance
“…In years 2017 and 2018, only one article is relevant according to research criteria, whereas in 2019, it increases to six, and in 2020, it is 19, which shows an upward trend. Previous studies done in the different fields of blockchain technology have also reported that blockchain technology is gaining attention and the number of publications is showing an upward trend (Pal et al, 2021;Rejeb et al, 2021;Cagigas et al, 2021). The interest of researchers, academicians and policymakers toward blockchain adoption is increasing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In years 2017 and 2018, only one article is relevant according to research criteria, whereas in 2019, it increases to six, and in 2020, it is 19, which shows an upward trend. Previous studies done in the different fields of blockchain technology have also reported that blockchain technology is gaining attention and the number of publications is showing an upward trend (Pal et al, 2021;Rejeb et al, 2021;Cagigas et al, 2021). The interest of researchers, academicians and policymakers toward blockchain adoption is increasing.…”
Section: Resultsmentioning
confidence: 99%
“…These theories have been used by various researchers in their study to adopt blockchain technology: UTAUT (Tran and Nguyen, 2020; Queiroz and Fosso Wamba, 2019; Queiroz et al , 2020; Francisco and Swanson, 2018; Caldarelli et al , 2020; Wong et al , 2020b; Arias-Oliva et al , 2019); TAM (Liu and Ye, 2021; Grover et al , 2019; Nuryyev et al , 2020; Palos-Sanchez et al , 2021; Gil-Cordero et al , 2020); technology–organization–environment (TOE) framework (Clohessy and Acton, 2019; Gökalp et al , 2020; Wong et al , 2020a; Orji et al , 2020; Vergouwen et al , 2020; Malik et al , 2021); TAM with TRI (Sohaib et al , 2020); TAM with diffusion of innovation (DOI) theory (Ullah et al , 2021; Lou and Li, 2017); TAM with TTF (Lian et al , 2020); TAM with TRI and TPB (Kamble et al , 2019); and UTAUT with TTF and ISS models (Alazab et al , 2021).…”
Section: Theoretical Background Of Adoption Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetric ciphers are relative to public-private key ciphers. In today's cryptographic techniques or schemes, symmetric cryptography and public-private key cryptosystems have their own advantages and disadvantages, so often in the same cryptographic technique or scheme, symmetric cryptography, and public-private key will appear in the same cryptographic technique or scheme at the same time [19].…”
Section: Symmetric Cryptography and Public-private Keymentioning
confidence: 99%
“…Blockchain technology can be described with five main elements – distribution, encryption, immutability, tokenization and decentralization (Wilkie and Smith, 2021). Furthermore, blockchain technology is based on five principles: computational logic, peer-to-peer transmission, irreversibility of records, distributed database and transparency with pseudonym (Pal et al , 2021). Information passes through three elements in a blockchain technology: system architecture, data recovery and communication (Yacoub and Castillo, 2021).…”
Section: Introductionmentioning
confidence: 99%